2013
DOI: 10.1103/physreve.88.062921
|View full text |Cite
|
Sign up to set email alerts
|

General multicomponent Yajima-Oikawa system: Painlevé analysis, soliton solutions, and energy-sharing collisions

Abstract: We consider the multicomponent Yajima-Oikawa (YO) system and show that the two-component YO system can be derived in a physical setting of a three-coupled nonlinear Schrödinger (3-CNLS) type system by the asymptotic reduction method. The derivation is further generalized to the multicomponent case. This set of equations describes the dynamics of nonlinear resonant interaction between a one-dimensional long wave and multiple short waves. The Painlevé analysis of the general multicomponent YO system shows that t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
60
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(66 citation statements)
references
References 69 publications
6
60
0
Order By: Relevance
“…(3) constitute the socalled multicomponent YO (mYO) system, originally introduced in the context of many-component magnon-phonon systems [42], which generalizes the YO model [43]. This model has recently attracted considerable attention due to its variety of solutions and interesting soliton collision properties [54][55][56]. Similarly to the single-component YO model, the mYO system is completely integrable, and possesses soliton solutions of the form [54]: n ∝ −sech 2 (K s X − Ω s T ) and q 0,+1 ∝ sech(K s X − Ω s T ), where K s , Ω s are constants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(3) constitute the socalled multicomponent YO (mYO) system, originally introduced in the context of many-component magnon-phonon systems [42], which generalizes the YO model [43]. This model has recently attracted considerable attention due to its variety of solutions and interesting soliton collision properties [54][55][56]. Similarly to the single-component YO model, the mYO system is completely integrable, and possesses soliton solutions of the form [54]: n ∝ −sech 2 (K s X − Ω s T ) and q 0,+1 ∝ sech(K s X − Ω s T ), where K s , Ω s are constants.…”
mentioning
confidence: 99%
“…This model has recently attracted considerable attention due to its variety of solutions and interesting soliton collision properties [54][55][56]. Similarly to the single-component YO model, the mYO system is completely integrable, and possesses soliton solutions of the form [54]: n ∝ −sech 2 (K s X − Ω s T ) and q 0,+1 ∝ sech(K s X − Ω s T ), where K s , Ω s are constants. When substituted into Eqs.…”
mentioning
confidence: 99%
“…Also, the dark (gray) solitons always undergo elastic collision. This study will find multifaceted applications, particularly in the context of optical computing [43], nonlinear optics [17,24,39,40,42], water wave theory [22,23] and also in multicomponent Bose-Einstein condensates [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kanna et al have shown that the following (1+1) dimensional (i.e. one time and one space dimensions) LSRI system [8] iS j,t + δS j,xx + LS j = 0, j = 1, 2, (1a)…”
Section: Introductionmentioning
confidence: 99%
“…In Ref. [8], we have obtained the bright n-soliton solution of the above system (1) and have revealed the fact that the bright solitons can undergo two types of fascinating energy sharing collisions. Here the presence of the long wave induces nonlinear interaction between two SWs which leads to nontrivial collision behaviour.…”
Section: Introductionmentioning
confidence: 99%